The impact of religiosity on fertility: a comparative analysis of France, Hungary, Norway, and Germany - Hubert, Sandra (Springer VS research, 2015)
Demographic patterns in comparative perspective.-Religion and religiosity -- How religious affiliation and religiosity affect fertility -- The national frame and individual characteristics.-Empirical analysis in comparative perspective